TLR9 stimulation induces increase in fungicidal activity of human dendritic cells challenged with Paracoccidioides brasiliensis - Vieira, Ivy Rafacho [UNESP] (2018)
Microorganisms killing by dendritic cells (DCs) is an important effector mechanism during innate immune response, as it can avoid dissemination of infection during migration of these cells toward draining lymph nodes. However, this function depends on pattern recognition receptors (PRRs) to which the microorganism will bind in these cells. Regarding this, TLR9 activation, by stimulating the oxidative metabolism, induces increase in microbicidal activity of these cells. Accordingly, we showed that DCs treatment with a TLR9 agonist results in an increase in fungicidal activity of these cells against the fungus Paracoccidioides brasiliensis (Pb), which however, was not associated to higher H 2 O 2 levels.